Economics of management in road transport industry - Arora, S. K. (Satish Kumar), 1941- (New Delhi : Deep & Deep Publications, 1987)
With reference to Punjab.
Includes index.
Bibliography: p. [209]-216.
Keywords: Transportation, Automotive -- India -- Punjab